2012
DOI: 10.3389/fphys.2012.00176
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nitric Oxide in the Dysregulation of the Urine Concentration Mechanism in Diabetes Mellitus

Abstract: Uncontrolled diabetes mellitus results in osmotic diuresis. Diabetic patients have lowered nitric oxide (NO) which may exacerbate polyuria. We examined how lack of NO affects the transporters involved in urine concentration in diabetic animals. Diabetes was induced in rats by streptozotocin. Control and diabetic rats were given L-NAME for 3 weeks. Urine osmolality, urine output, and expression of urea and water transporters and the Na-K-2Cl cotransporter were examined. Predictably, diabetic rats presented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…In this study, there was no comparison to diabetic rats treated with insulin, so it is not known whether the decrease of blood glucose upon dapagliflozin treatment might contribute to UT-A1 up-regulation in diabetic rat IM. However, our previous study showed that absence of nitric oxide (NO) production in kidney reduced UT-A1 protein abundance in DM[29]. Hyperglycemia is believed to play a key role in reducing NO production in kidney[30].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, there was no comparison to diabetic rats treated with insulin, so it is not known whether the decrease of blood glucose upon dapagliflozin treatment might contribute to UT-A1 up-regulation in diabetic rat IM. However, our previous study showed that absence of nitric oxide (NO) production in kidney reduced UT-A1 protein abundance in DM[29]. Hyperglycemia is believed to play a key role in reducing NO production in kidney[30].…”
Section: Discussionmentioning
confidence: 99%
“…In opposition to us, a recent work showed an up regulation of glycosylated AQP2 in STZ-diabetic rats and found that the treatment of the animals with L-NAME suppressed the compensatory increase in AQP2 expression [48]. However, that study was performed three weeks after the induction of diabetes and the authors attributed the effect of L-NAME to the inhibition of vasopressin release.…”
Section: Discussionmentioning
confidence: 83%
“…This enhanced production leads to hyperfiltration and microalbuminuria characterizing early diabetic nephropathy [22,23]. Progression towards end-stage kidney disease is accompanied by a decrease in NO bioavailability, mainly due to excessive accumulation of advanced glycation end products [24,25].…”
Section: Discussionmentioning
confidence: 99%